PROBLEMS OF IMPLEMENTATION OF THE LESSOR'S SOME OBLIGATIONS UNDER THE LEASE AGREEMENT - Guliyeva Shafa Teyyub, (International Journal of Innovative Technologies in Social Science, 2023)
According to its subject, the history of the regulation of the leasing contract, which belongs to one of the types of contracts on the use of property, in the legislation and practice of Azerbaijan, is still short. So, when the Republic of Azerbaijan was part of the Soviet Union, this agreement was not in our legislation. This contract, which was implemented after Azerbaijan gained independence, was previously regulated by the Law on "Leasing Service" dated 1994. In practice, the first Azerbaijani leasing companies were established in those 90s. However, the law intended for the transitional period did not meet all the requirements, so it was soon repealed, that is, in the early 2000s. Currently, this contract is regulated by norms systematized in a separate chapter of the Civil Code of the Republic of Azerbaijan.